A Review of the technologies for mapping within-field variability - Godwin, R. J.; Miller, P. C. H. (Elsevier, 2003)
Techniques for mapping soil physical and chemical condition, topography and the weed status of fields, are reviewed from a practical and economic perspective. The conclusions are that it is possible to target sample the soil physical and chemical status of fields and locate areas of high weed density following the use of inexpensive, non-invasive techniques electromagnetic induction (EMI) aerial digital photography (ADP) and radiometry. Semi-automated field reconnaissance systems on all terrain vehicles and combines also assist in locating the position of weed patches. P and K fertiliser can be replenished by using the â off-takeâ values determined from yield maps, whilst crop density in the spring period shows potential for the management of nitrogen fertiliser in cereal crops using ADP and could also be a benefit in the application of agrochemicals. Currently, the most economically viable method to determine field topography is to use very simple surveying techniques, and there is potential to automate this.